PENGOLAHAN LIMBAH RUMAH TANGGA DENGAN MENGGUNAKAN BUFFLED UP-FLOW REACTOR - Wuryani Artiningsih; Rita Dewi Triastianti (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2018)
Environmental problems occur because the act of a human hand which then cause disturbance to the environment. Household or domestic activities such as can be and has been shown to cause a decline in water quality. With increasing liquid waste disposal, pollution is increasing so that pollute the environment. Therefore, the authors wish to conduct research of domestic waste water with the aim to reduce levels of phosphate, nitrite and detergent. In domestic wastewater/sewage household, the authors chose to use anaerobic processing using buffled up-flow reactor were made ​​using glass with a length of 100cm, width 25 cm and height 30 cm. The results obtained for the effluent phosphate levels for 0.3502 mg/L on the second replay (the second day), nitrite by 0.1206 mg/L on the second replay (the second day) and detergent was 0.2799 mg/L in the first repeat (on the first day) in terms of the processing of the buffled up-flow reactor capable of lowering the levels of phosphate, nitrite and detergent in water and wastewater. Removal efficiency obtained from the results of wastewater treatment with bufffled up-flow reactor for phosphate content of 47.3%,-13.30% and detergents nitrite 57.8%.